Factors Affecting The Outcome of in Vitro Fertilization (IVF) - Fayka Putri Poempida; Jimmy Yanuar; Hamdani Lunardhi; Samsulhadi Samsulhadi; Relly Y. Primariawan (Syntax Corporation, 2022)
The high prevalence of infertility motivated researchers to find a solution, henceforth In Vitro Fertilization was invented. Factors that affect the outcome of IVF may include sperm analysis, maternal Body Mass Index (BMI), maternal smoking habits, endometriosis, and maternal age. However, there are ongoing debates about the role of said factors regarding the outcome of IVF. The objective of this research is to analyze those factors. This research is a Case-Control study with an analytical observational design. Data were retrieved from patients’ medical records undergoing IVF in Graha Amerta Fertility Clinic from January 2019-October 2020. First, the Chi-Square Test revealed sperm abnormality (p=0.212), Maternal BMI (p=0.427), endometriosis (p=0.067), meaning there was no connection with the outcome of IVF. Simultaneously, maternal age (p=0.037) showed a connection with the outcome of IVF. From the Binary Logistic Regression Test, maternal age 36-40 years old (p=0.044) affects the outcome of IVF significantly. Concurrently maternal BMI, endometriosis, and sperm abnormality have p value>0.05 meaning it is insignificant to the outcome of IVF. This research concluded that sperm abnormality, maternal BMI, and endometriosis do not affect the outcome of IVF. There was no data about maternal smoking habits. Whilst maternal age affects the outcome of IVF. Conclusion: This research concluded that sperm abnormality, maternal BMI, and endometriosis do not affect the outcome of IVF. There was no data about maternal smoking habits. Whilst maternal age affects the outcome of IVF.